Progress in organic solar cells: Materials, challenges, and novel strategies for niche applications - Julio C. Carrillo-Sendejas; José-Luis Maldonado (APL Energy)
Organic solar cells (OSCs) are emerging as a viable alternative, and complementary niche of applications, to the conventional silicon-based photovoltaics due to their unique attributes, including flexibility, lightweight, semitransparency, and ease of processing. Recent breakthroughs in non-fullerene acceptors and advanced polymer donors have led to power conversion efficiencies exceeding 20%, closing the gap with traditional technologies. These advancements are driven by innovations in material design and engineering, enhanced understanding of device morphology, and improvements in fabrication architectures, as well as state-of-the-art characterization techniques. Despite these achievements, significant challenges remain, such as improving long-term device stability under environmental stress, upscaling OSCs from lab-scale devices to large-area modules through printing technologies, and achieving cost-effective scalability for mass production. This review also highlights OSCs’ transformative potential in niche applications such as semi-transparent photovoltaic windows, flexible/wearable electronics, and agricultural systems, paving the way for alternative sustainable and multifunctional energy solutions.